REVITALIZING FOREST MANAGEMENT IN INDONESIAN FOREST INDUSTRY POST-COVID-19: EXPECTATIONS FROM YOUNG FORESTERS (A CASE STUDY FROM UNIVERSITY STUDENTS) - Daniel, David Jhon; Yovi, Efi Yuliati (Association of Indonesian Forestry and Environment Researchers and Technicians, 2024)
The global health emergency triggered by COVID-19 has had a significant impact on Indonesia's forestry industry. This study investigates the expectations of young foresters regarding the post-pandemic landscape, exploring various aspects such as industry performance, focus, worker protection, global strategies, and personal views on the industry's future. In conjunction with descriptive statistics, word cloud analysis was employed to identify salient issues drawing substantial attention. Through purposive sampling at a leading forestry university in Indonesia, the study reveals that young foresters perceive the transition towards developing industries based on non-timber forest products and environmental services as potential areas of growth. However, they acknowledge that the timber-based industry has historically been the backbone of Indonesia's forest industry and is likely to maintain its significance as forest management trends toward plantation forestry. Additionally, the study demonstrates the enduring appeal of the forestry sector to the younger generation, positioning it as a valuable entrepreneurial field.